Os efeitos da política monetária na estrutura a termo de taxas de juros brasileira, no período de julho de 1999 a março de 2007 - Câmara Filho, Raimundo (2007)
Monetary policy actions are believed to be transmitted to the economy through their effects on market interest rates. However, it is observed that the relationship between monetary policy and market interest rates seems quite complex. Although casual observation suggests a close connection between monetary policy actions and short-term interest rates, the relationship between policy actions and long-term interest rates is not so evident. This study estimates the response of the Brazilian term structure of interest rates, from the implementation of the Inflation Targeting Regime until March 2007. Using a model that captures the tendency of market rates to anticipate policy actions, this study finds evidence of a stronger response of long-term rates to innovations in the Selic rate than found in previous research.